Water-based binder as well as preparation method and application thereof
The aqueous binder prepared by crosslinking sodium carboxymethylcellulose with crosslinking agents such as polyacrylic acid and polyvinyl alcohol has been solved, and a negative electrode sheet with high bonding force, flexibility and circulation stability is achieved.
Patent Information
- Application Number
- CN202411753953.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-14
AI Technical Summary
The carboxymethylcellulose (CMC) and polyacrylic acid (PAA)-type binders used in existing lithium-ion batteries have insufficient processing and circulation performance, resulting in poor flexibility and poor circulation performance of the negative electrode sheet.
By using the preparation method of an aqueous binder, sodium carboxymethylcellulose is crosslinked with polyacrylic acid, polyvinyl alcohol, etc. as a crosslinking agent to form a polymer binder with a three-dimensional crosslinking network.
It improves the bonding performance and flexibility of the adhesive, enhances the circulation performance and electrochemical stability of the negative electrode sheet, and reduces the amount of adhesive.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an aqueous binder and a preparation method and application thereof. Background Art
[0002] In recent years, lithium-ion batteries have been closely related to our lives. From portable electronic devices, computers to electric vehicles and large-scale energy storage systems, lithium-ion batteries have shown broad application prospects and market value. Today's lithium-ion batteries are developing towards extended cycle stability, high energy density, high transmission rate capability, low cost and safety.
[0003] The amount of binder used in lithium-ion batteries is less than 5%, but it plays an important role. It can bind and maintain the active material and strengthen the contact between the active material and the conductive agent. At the same time, it can bind the active material to the current collector. During the charge and discharge process, the electrode often shrinks and expands in volume. At this time, the binder will play an excellent protective role. The stability of the battery, irreversible capacity loss and other electrochemical properties are inseparable from the binder. Therefore, the binder as a key auxiliary material has become an important research direction.
[0004] At present, the negative electrode sheets made of carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) binders commonly used in the commercial market have poor flexibility and processing performance, and the structure of the negative electrode sheets may be destroyed during processing. In industrial production, these two binders are often mixed with SBR to solve the problem of electrode sheet processing, but SBR swells greatly in the electrolyte and has poor cycle performance.
[0005] Therefore, it is still necessary to develop a binder that combines bonding properties, flexibility and cycle performance to meet the application requirements of high-performance lithium-ion batteries. Summary of the invention
[0006] In order to solve at least one of the above technical problems, the present invention provides a water-based binder and a preparation method and application thereof.
[0007] As one aspect, the present invention provides an aqueous binder, which is a cross-linked product of sodium carboxymethyl cellulose, a first cross-linking agent and a second cross-linking agent; wherein the first cross-linking agent and the second cross-linking agent are selected from any two of polyacrylic acid, polybutyl acrylate, polyvinyl alcohol, polyamide, polyimide, and polyacrylamide.
[0008] In some embodiments of the present invention, the mass ratio of sodium carboxymethyl cellulose, the first cross-linking agent and the second cross-linking agent is 1:(0.5-3):(0.5-3).
[0009] In some embodiments of the present invention, the first crosslinking agent and the second crosslinking agent are polyvinyl alcohol and polyacrylamide; and / or the molecular weight of sodium carboxymethyl cellulose is 7×10 5 ~9×10 5 , for example, can be 7.2×10 5 , 7.6×10 5 , 7.8×10 5 , 8.3×10 5 , 8.6×10 5 , 8.9×10 5 etc.; and / or, the molecular weight of the first cross-linking agent is 4×10 4 ~5×10 4 , for example, can be 4.2×10 5 , 4.3×10 5 , 4.6×10 5 , 4.7×10 5 , 4.8×10 5 , 4.9×10 5 etc.; and / or, the molecular weight of the second cross-linking agent is 4×10 6 ~5.5×10 6 , for example, can be 4.2×10 5 , 4.4×10 5 , 4.8×10 5 , 5.1×10 5 , 5.3×10 5 , 5.4×10 5 wait.
[0010] As another aspect, the present invention provides a method for preparing the above-mentioned aqueous binder, and the method for preparing the aqueous binder comprises: preparing an aqueous solution of sodium carboxymethyl cellulose; adding a first cross-linking agent, a second cross-linking agent and an initiator to the aqueous solution of sodium carboxymethyl cellulose respectively to obtain a mixed solution; heating the mixed solution in an inert atmosphere; and adjusting the pH value of the reaction solution to neutral after the reaction is completed to obtain an aqueous binder.
[0011] In some embodiments of the present invention, in the mixed solution, the mass ratio of sodium carboxymethyl cellulose, the first cross-linking agent and the second cross-linking agent is 1:(0.5-3):(0.5-3).
[0012] In some embodiments of the present invention, in the step of heating the mixed solution for reaction, the reaction temperature is 40-60° C., the reaction time is 60-100 min, and / or the alkaline solution is selected from any one of sodium hydroxide solution and potassium hydroxide solution.
[0013] In some embodiments of the present invention, the initiator includes at least one combination of benzoyl peroxide / sucrose, tert-butyl hydroperoxide / bleaching powder, tert-butyl hydroperoxide / sodium metabisulfite, benzoyl peroxide / N,N-dimethylaniline, ammonium persulfate / sodium bisulfite, potassium persulfate / sodium bisulfite, hydrogen peroxide / tartaric acid, hydrogen peroxide / bleaching powder, ammonium persulfate / ferrous sulfate, hydrogen peroxide / ferrous sulfate, benzoyl peroxide / N,N-diethylaniline, benzoyl peroxide / ferrous pyrophosphate, and potassium persulfate / ferrous chloride.
[0014] As another aspect, the present invention provides a negative electrode plate, which comprises the above-mentioned aqueous binder or the aqueous binder obtained by the preparation method of the above-mentioned aqueous binder.
[0015] In some embodiments of the present invention, the active material of the negative electrode plate is graphite.
[0016] As another aspect, the present invention provides a lithium-ion battery, which includes the above-mentioned negative electrode plate.
[0017] The technical solution provided by the embodiment of the present invention has the following advantages:
[0018] The water-based binder of the embodiment of the present invention uses two cross-linking agents (i.e., the first cross-linking agent and the second cross-linking agent) as cross-linking materials, and under the action of an initiator, forms a polymer with a three-dimensional cross-linked network by grafting and cross-linking with sodium carboxymethyl cellulose. The prepared polymer has excellent elasticity and toughness as a water-based binder, and has a greater ability to withstand expansion strain. The present invention can effectively solve the problem of poor flexibility of commercial carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) binders, and further improves the bonding performance, can reduce the amount of binder used, and improve the cycle performance of the battery.
[0019] When the aqueous binder of the embodiment of the present invention is used to prepare the negative electrode sheet whose active material is graphite, the polyvinyl alcohol and polyacrylamide in the aqueous binder, as functional binders, can form strong interactions such as hydrogen bonds and covalent bonds with the graphite surface, and tightly adhere the graphite to the surrounding. Specifically, polyvinyl alcohol can be cross-linked with sodium carboxymethyl cellulose molecules through free radical polymerization, or it can form ether bonds through the condensation of the hydroxyl groups on the surface with the hydroxyl groups of sodium carboxymethyl cellulose, which can form a three-dimensional cross-linked network with excellent elasticity and toughness; the abundant hydroxyl groups in the polyvinyl alcohol molecular chain can form hydrogen bonds on the surface of the graphite negative electrode, and have good adhesion. The introduction of polyacrylamide increases the polar functional groups of the binder, which can form hydrogen bonding forces and dipole forces with the surrounding materials, which is beneficial to improving the stability of the electrode sheet structure and the wettability of the electrolyte. DETAILED DESCRIPTION
[0020] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0021] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.
[0022] According to an embodiment of one aspect of the present invention, an aqueous binder is provided, which is a cross-linked product of sodium carboxymethyl cellulose, a first cross-linking agent and a second cross-linking agent; wherein the first cross-linking agent and the second cross-linking agent are selected from any two of polyacrylic acid, polybutyl acrylate, polyvinyl alcohol, polyamide, polyimide and polyacrylamide.
[0023] The aqueous binder of the embodiment of the present invention cross-links the cross-linking agent into the cellulose matrix of sodium carboxymethyl cellulose through an initiator to form a three-dimensional cross-linked binder network, thereby improving the bonding performance and flexibility of the sodium carboxymethyl cellulose binder.
[0024] In some embodiments of the present invention, the aqueous binder is an aqueous binder for a negative electrode of a lithium-ion battery.
[0025] In some embodiments of the present invention, a raw material for preparing an aqueous binder for a negative electrode of a lithium-ion battery includes: a binder sodium carboxymethyl cellulose matrix, a first crosslinking agent polyvinyl alcohol and a second crosslinking agent polyacrylamide, and an initiator tert-butyl hydroperoxide / sodium pyrosulfite. In the preparation method of the aqueous binder for the negative electrode of a lithium-ion battery, two crosslinking agents are crosslinked to the cellulose matrix of sodium carboxymethyl cellulose by an initiator to form a three-dimensional crosslinked binder network, thereby improving the bonding performance and flexibility of the sodium carboxymethyl cellulose binder.
[0026] In some embodiments of the present invention, a method for preparing an aqueous binder comprises the following steps:
[0027] (1) dissolving a binder sodium carboxymethyl cellulose matrix in deionized water and stirring to obtain a uniform and stable viscous solution;
[0028] (2) adding a first crosslinking agent, a second crosslinking agent, and an initiator one by one to the aqueous solution of sodium carboxymethyl cellulose obtained in step (1) to obtain a mixed solution, and introducing nitrogen gas to remove oxygen in the solution;
[0029] (3) heating the mixed solution obtained in step (2) to a certain temperature under continuous nitrogen purge to react, and stopping heating after a period of reaction;
[0030] (4) The pH value of the solution obtained in step (3) is adjusted with an alkaline solution to reach neutrality to obtain a water-based adhesive.
[0031] In some embodiments of the present invention, in the mixed solution obtained in step (2), the mass ratio of sodium carboxymethyl cellulose, the first cross-linking agent and the second cross-linking agent is 1:(0.5-3):(0.5-3); for example, it can be 1:0.61:0.72, 1:0.82:0.93, 1:1.1:0.9, 1:1.62:1.43, 1:1.76:2.14, 1:2.64:2.82, 1:2.79:2.93, etc.
[0032] In some embodiments of the present invention, in step (2), the first crosslinking agent and the second crosslinking agent are selected from polyacrylic acid, polybutyl acrylate, polyvinyl alcohol, polyamide (C6H 11 NO) n ), any two of polyimide and polyacrylamide.
[0033] In some embodiments of the present invention, in step (2), the initiator includes at least one combination of benzoyl peroxide / sucrose, tert-butyl hydroperoxide / bleaching powder, tert-butyl hydroperoxide / sodium metabisulfite, benzoyl peroxide / N,N-dimethylaniline, ammonium persulfate / sodium bisulfite, potassium persulfate / sodium bisulfite, hydrogen peroxide / tartaric acid, hydrogen peroxide / bleaching powder, ammonium persulfate / ferrous sulfate, hydrogen peroxide / ferrous sulfate, benzoyl peroxide / N,N-diethylaniline, benzoyl peroxide / ferrous pyrophosphate, and potassium persulfate / ferrous chloride; wherein, “ / ” means “and”.
[0034] In some embodiments of the present invention, in step (3), in the step of heating the mixed solution for reaction, the reaction temperature is 40-60°C, for example, it can be 42°C, 48°C, 51°C, 56°C, 59°C, etc.; the reaction time is 60-100 min, for example, it can be 61 min, 72 min, 83 min, 89 min, 98 min, etc.
[0035] In some embodiments of the present invention, in step (4), the alkaline solution is selected from any one of a sodium hydroxide solution and a potassium hydroxide solution.
[0036] In order to further illustrate the effect of the present invention, specific embodiments are used for illustration below.
[0037] All reagents used in the following examples and comparative examples are commercially available reagents. The detailed information of each reagent is as follows:
[0038] Sodium carboxymethyl cellulose: CAS No. 9004-32-4, brand C804626, viscosity range of 1% aqueous solution 3000-5000 mPa·s, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0039] Polyvinyl alcohol: CAS No. 9002-89-5, brand P816865, molecular weight about 47000, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0040] Polyacrylamide: CAS No. 9003-05-8, brand P888782, molecular weight about 5 million, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0041] Tert-butyl hydroperoxide: CAS No. 75-91-2, brand No. B802372, aqueous solution, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0042] Sodium metabisulfite: CAS No. 7681-57-4, brand S818096, purity ≥ 99%, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0043] Conductive agent: Conductive carbon black (Super P), brand C01, purchased from Jiangxi Jinxi Nanomaterials Co., Ltd.
[0044] Lithium sheet: size 16*1mm, purchased from Xinghua Note Battery Material Co., Ltd.;
[0045] Copper foil: average thickness of 9 μm, purchased from Dongguan Notong Metal Materials Co., Ltd.
[0046] Diaphragm: Celgard2325, average thickness 60 mm, purchased from Tianjin Annuohe New Energy Technology Co., Ltd.;
[0047] Electrolyte: A mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) (the volume ratio of EC to DEC is 1:1) containing 1 mol / L lithium hexafluorophosphate (LiPF6).
[0048] Example 1
[0049] A method for preparing a water-based binder comprises the following steps:
[0050] (1) Dissolve 1 g of sodium carboxymethyl cellulose in 60 mL of deionized water and stir with a magnetic stirrer at room temperature for 2 hours to obtain a transparent viscous solution;
[0051] (2) adding 1.5 g polyacrylamide, 1.5 g polyvinyl alcohol, and tert-butyl hydroperoxide / sodium metabisulfite (0.05 g / 0.03 g) to the aqueous solution of sodium carboxymethyl cellulose obtained in step (1), and passing nitrogen gas to purge for 6 h;
[0052] (3) Continue to introduce nitrogen, heat to 50°C under nitrogen purge, and continue stirring for 4 h;
[0053] (4) Add NaOH to the solution obtained in step (3), adjust the pH to 7, and prepare a water-based binder.
[0054] Example 2
[0055] Except that the ratio of sodium carboxymethyl cellulose, polyacrylamide and polyvinyl alcohol is set to 1:3:3; specifically, 1 g of sodium carboxymethyl cellulose, 3 g of polyacrylamide and 3 g of polyvinyl alcohol, the remaining steps are the same as those in Example 1.
[0056] Example 3
[0057] Except that “the ratio of sodium carboxymethyl cellulose, polyacrylamide and polyvinyl alcohol is set to 1:0.5:0.5; specifically, 1 g of sodium carboxymethyl cellulose, 0.5 g of polyacrylamide and 0.5 g of polyvinyl alcohol”, the remaining steps are the same as those in Example 1.
[0058] Example 4
[0059] Except that “the ratio of sodium carboxymethyl cellulose, polyacrylamide and polyvinyl alcohol is set to 1:1:1; specifically, 1 g of sodium carboxymethyl cellulose, 1 g of polyacrylamide and 1 g of polyvinyl alcohol”, the remaining steps are the same as those in Example 1.
[0060] Example 5
[0061] Except that the ratio of sodium carboxymethyl cellulose, polyacrylamide and polyvinyl alcohol is set to 1:3:0.5; specifically, 1 g of sodium carboxymethyl cellulose, 3 g of polyacrylamide and 0.5 g of polyvinyl alcohol, the remaining steps are the same as those in Example 1.
[0062] Example 6
[0063] Except that the ratio of sodium carboxymethyl cellulose, polyacrylamide and polyvinyl alcohol is set to 1:0.5:3; specifically, 1 g of sodium carboxymethyl cellulose, 0.5 g of polyacrylamide and 3 g of polyvinyl alcohol, the remaining steps are the same as those in Example 1.
[0064] Comparative Example 1
[0065] The binder is sodium carboxymethyl cellulose.
[0066] Comparative Example 2
[0067] The binder is polyacrylamide.
[0068] Comparative Example 3
[0069] The binder is polyvinyl alcohol.
[0070] Comparative Example 4
[0071] A method for preparing a water-based binder comprises the following steps:
[0072] (1) Dissolve 1 g of sodium carboxymethyl cellulose in 60 mL of deionized water and stir with a magnetic stirrer at room temperature for 2 hours to obtain a transparent viscous solution;
[0073] (2) adding 3 g of polyacrylamide and tert-butyl hydroperoxide / sodium metabisulfite (0.05 g / 0.03 g) to the aqueous solution of sodium carboxymethyl cellulose obtained in step (1), and passing nitrogen gas for 6 h;
[0074] (3) Continue to introduce nitrogen, heat to 50°C under nitrogen purge, and continue stirring for 4 h;
[0075] (4) Add NaOH to the solution obtained in step (3), adjust the pH to 7, and prepare a water-based binder.
[0076] Comparative Example 5
[0077] A method for preparing a water-based binder comprises the following steps:
[0078] (1) Dissolve 1 g of sodium carboxymethyl cellulose in 60 mL of deionized water and stir with a magnetic stirrer at room temperature for 2 hours to obtain a transparent viscous solution;
[0079] (2) adding 3 g of polyvinyl alcohol and tert-butyl hydroperoxide / sodium metabisulfite (0.05 g / 0.03 g) to the aqueous solution of sodium carboxymethyl cellulose obtained in step (1), and passing nitrogen gas for 6 h;
[0080] (3) Continue to introduce nitrogen, heat to 50°C under nitrogen purge, and continue stirring for 4 h;
[0081] (4) Add NaOH to the solution obtained in step (3), adjust the pH to 7, and prepare a water-based binder.
[0082] Performance Testing
[0083] The slurry and electrode prepared by the above-mentioned binder were subjected to slurry stability test, bonding strength, flexibility and electrochemical performance test. The specific test steps are as follows:
[0084] (1) Preparation of negative electrode slurry: Graphite, conductive carbon black, and negative electrode binders of each group of embodiments and comparative examples were mixed in a mass ratio of graphite: conductive carbon black: aqueous binder of 96:1:3; then, the mixture was uniformly dispersed in an appropriate amount of deionized water by stirring, and the solid content of the slurry was 40-50%, to obtain a uniformly mixed lithium ion battery negative electrode slurry with a viscosity of 3000-5000.
[0085] (2) Stability test of negative electrode slurry: The viscosity of the negative electrode slurry obtained by the test is recorded as a; the slurry is left to stand for 12 hours, and the viscosity of the slurry is tested and recorded as b. The test shows that the ratio of the viscosity increase of the negative electrode slurry within 12 hours is c = (ba) / a * 100, and the test results are shown in Table 1.
[0086] (3) Preparation of graphite negative electrode sheet: The lithium-ion battery negative electrode slurry is evenly coated on a 9-micron thick copper foil using an automatic coating machine, with a coating surface density of 0.05 g / cm 2 , and then placed in a vacuum drying oven to dry and remove the solvent; after drying, the negative electrode sheet is obtained.
[0087] (4) Graphite negative electrode sheet peeling strength test: The prepared graphite negative electrode sheet was cut into 10 cm × 2 cm strips. One side of the coated side was adhered to a 1 mm thick steel plate with double-sided tape, and the other side was clamped with a tensile testing machine fixture. The strip was peeled off in the 180° direction at a speed of 100 mm / min, and the peeling stress was measured. The test results are shown in Table 1.
[0088] (5) Flexibility test of graphite negative electrode: The obtained graphite negative electrode was bent around a glass rod with a diameter of 5 mm. After bending, it was flattened and the state of the electrode was observed under an optical microscope. The electrode was marked as "√" if it was intact, and marked as "×" if it was powdered, cracked or fell off. The test results are shown in Table 1.
[0089] (6) Electrochemical performance test: The prepared graphite negative electrode sheet was punched into a 10 mm diameter disc using a punching machine and transferred to a glove box filled with argon. A pure lithium sheet was used as the counter electrode and Celgard 2325 was used as the separator. The electrolyte was a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) (the volume ratio of EC and DEC was 1:1) containing 1 mol / L lithium hexafluorophosphate (LiPF6) and assembled into a 2032 button half-cell. The assembled button half-cell was left to stand for 12 h. In the test, the lithium sheet side was used as the low potential side and the graphite electrode sheet was used as the high potential side. In the voltage range of 0.01 to 2.5 V, the charge and discharge was performed at a rate of 0.1C for one cycle and then at a rate of 1C for a cyclic charge and discharge test. The capacity retention rate data was obtained after 500 cycles of testing. The test results are shown in Table 1.
[0090] Through the above data analysis, we can draw the following conclusions:
[0091] (1) According to the data analysis of Example 1, Example 3 and Comparative Example 1, it can be concluded that as the content of sodium carboxymethyl cellulose decreases, the peel strength of the graphite negative electrode sheet decreases, and the flexibility of the graphite negative electrode sheet also decreases, indicating that the two cross-linking agents are helpful in maintaining the flexibility of the negative electrode sheet;
[0092] (2) According to the data analysis of Example 1, Example 2, Comparative Example 2 and Comparative Example 3, it can be concluded that as the cross-linking agent content increases, the stability of the negative electrode slurry gradually decreases. After completely eliminating sodium carboxymethyl cellulose, the slurry viscosity increases too much and can no longer meet the production requirements of lithium-ion battery negative electrode sheets.
[0093] (3) According to the data analysis of Examples 1 to 6, the following conclusions can be drawn: the stability of the negative electrode slurry is not much different when the ratio of sodium carboxymethyl cellulose to the cross-linking agent is different, but the current ratio of 1:1.5:1.5 has the most obvious effect on improving the battery cycle stability.
[0094] Table 1 Performance test results of different water-based binders
[0095] sample Viscosity increase ratio Peel strength (N / cm) Flexibility Cycle capacity retention rate Example 1 18.0% 27 √ 92.6% Example 2 28.4% 32 √ 90.6% Example 3 16.3% 18 √ 91.4% Example 4 16.2% 22 √ 92.2% Example 5 20.4% 28 √ 89.6% Example 6 21.3% 24 √ 88.7% Comparative Example 1 11.9% 8 × 79.7% Comparative Example 2 51.5% 38 √ 84.%% Comparative Example 3 57.6% 20 √ 82.8% Comparative Example 4 19.5% 28 √ 87.6% Comparative Example 5 18.7% 30 √ 85.3%
[0096] In summary, the aqueous binder of the present invention and its preparation method and application, the aqueous binder is prepared by cross-linking sodium carboxymethyl cellulose, a first cross-linking agent and a second cross-linking agent to form a cross-linked product. The prepared aqueous binder has higher bonding force, high flexibility and cycle life than commercial carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) aqueous binders, and can effectively improve the electrochemical performance of lithium ion batteries; when the aqueous binder is used as a negative electrode binder for lithium ion batteries, a negative electrode sheet with high bonding force and high cycle performance can be obtained.
[0097] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0098] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments described herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A water-based adhesive, characterized in that: The aqueous binder is a cross-linked product of sodium carboxymethyl cellulose, a first cross-linking agent and a second cross-linking agent; Wherein, the first cross-linking agent and the second cross-linking agent are selected from any two of polyacrylic acid, polybutyl acrylate, polyvinyl alcohol, polyamide, polyimide, and polyacrylamide.
2. The aqueous adhesive according to claim 1, characterized in that The mass ratio of the sodium carboxymethyl cellulose, the first cross-linking agent and the second cross-linking agent is 1:(0.5-3):(0.5-3).
3. The aqueous adhesive according to claim 1 or 2, characterized in that: The first cross-linking agent and the second cross-linking agent are polyvinyl alcohol and polyacrylamide; And / or, the molecular weight of the sodium carboxymethyl cellulose is 7×10 5 ~9×10 5 ; And / or, the molecular weight of the first cross-linking agent is 4×10 4 ~5×10 4 ; And / or, the molecular weight of the second cross-linking agent is 4×10 6 ~5.5×10 6 .
4. A method for preparing the aqueous binder according to any one of claims 1 to 3, characterized in that: The preparation method of the aqueous binder comprises: preparing an aqueous solution of sodium carboxymethyl cellulose; Adding the first cross-linking agent, the second cross-linking agent and the initiator to the aqueous solution of sodium carboxymethyl cellulose to obtain a mixed solution; In an inert atmosphere, heating the mixed solution for reaction; After the reaction is completed, the pH value of the reaction solution is adjusted to neutral to obtain a water-based adhesive.
5. The method for preparing the aqueous binder according to claim 4, characterized in that: In the mixed solution, the mass ratio of sodium carboxymethyl cellulose, the first cross-linking agent and the second cross-linking agent is 1:(0.5-3):(0.5-3).
6. The method for preparing the aqueous binder according to claim 4 or 5, characterized in that: In the step of heating the mixed solution, the reaction temperature is 40 to 60° C. and the reaction time is 60 to 100 min; And / or, the alkaline solution is selected from any one of a sodium hydroxide solution and a potassium hydroxide solution.
7. The method for preparing the aqueous binder according to any one of claims 4 to 6, characterized in that: The initiator comprises at least one combination of benzoyl peroxide / sucrose, tert-butyl hydroperoxide / bleaching powder, tert-butyl hydroperoxide / sodium metabisulfite, benzoyl peroxide / N,N-dimethylaniline, ammonium persulfate / sodium bisulfite, potassium persulfate / sodium bisulfite, hydrogen peroxide / tartaric acid, hydrogen peroxide / bleaching powder, ammonium persulfate / ferrous sulfate, hydrogen peroxide / ferrous sulfate, benzoyl peroxide / N,N-diethylaniline, benzoyl peroxide / ferrous pyrophosphate, and potassium persulfate / ferrous chloride.
8. A negative electrode plate, characterized in that: The negative electrode plate comprises the aqueous binder according to any one of claims 1 to 3 or the aqueous binder obtained by the preparation method of the aqueous binder according to any one of claims 4 to 7.
9. The negative electrode sheet according to claim 8, characterized in that: The active material of the negative electrode plate is graphite.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet according to claim 8 or 9.
Citation Information
Cited By
Aqueous binder based on multivalent metal ion coordination crosslinking and preparation method and application thereof
CN121555109A